Fractionation of flavonols and anthocyanins in winemaking residues using molecularly imprinted cellulose‐synthetic hybrid particles with pyridyl active surface - Gomes, Catarina P. (2024)
Hybrid cellulose-synthetic particles with surface active pyridyl moieties and molecularly imprinted cavities for quercetin were prepared via atom transfer radical polymerization. The functionalization of the materials with pyridyl groups was confirmed by FTIR and the SEM micrographs of the hybrid particles demonstrate a clear surface modification compared with the pristine cellulose. Competitive sorption/desorption testing of the imprinted and non-imprinted particles with standard polyphenols show the achievement of an imprinting factor IF similar to 8. Moreover, it was also confirmed the high retention capability of the hybrid materials for polyphenols, due to their strong binding with the surface pyridyl moieties, even when using hydroalcoholic solvents of high ethanol content (e.g., ethanol/water 80/20 v/v). The sorption capabilities of the synthesized materials for polyphenols were explored with the fractionation of flavonols and anthocyanins in winemaking residues. High concentration and enrichment factors were achieved for high-added value compounds, namely five times for quercetin and 12 for quercetin-3-O-glucuronide with a diatomaceous earth extract and up to 4 for flavonols in a grape pomace (e.g. myricetin and quercetin glucosides). This research demonstrates de feasibility for the combination between the development of engineered materials addressing sustainability with their application to the valorization of agro-industrial wastes.